Empowering Equality: Addressing Women’s Underrepresentation in Indian Politics - Dhruvi Karia, (Indian Journal of Social Science and Literature (IJSSL), 2025)
Equality and fairness are values that we uphold in the modern period. Even Nevertheless, there has been a disproportionate amount of progress made in the global representation of women in politics. Women still confront significant impediments to entering political venues, whether they are in the quiet corners of rural communities or the busy streets of metropolises. Women's potential as leaders and change makers is hampered by the continued existence of discriminatory legislation, cultural norms, and structural biases. If things continue as they are, gender equality in the top positions of power won't be achieved for 130 years, according to UN Women. Women have been involved in politics since the colonial era, both with and without the right to vote. They have worked for and against the revolution by their words, deeds, and labor; yet, it is concerning that they are underrepresented in today's political environment. Thus, using qualitative research methodologies, this study aims to investigate women's political leadership in both the lower and upper houses of parliament, the percentage of women voters nationwide, and women's political awareness.